Difference between revisions of "2011 AMC 12B Problems/Problem 1"

m (added solutions header)
 
(9 intermediate revisions by 4 users not shown)
Line 2: Line 2:
 
What is <math>\frac{2+4+6}{1+3+5} - \frac{1+3+5}{2+4+6}?</math>
 
What is <math>\frac{2+4+6}{1+3+5} - \frac{1+3+5}{2+4+6}?</math>
 
   
 
   
<math>
+
<math>\textbf{(A)}\ -1 \qquad
\textbf{(A)}\ -1 \qquad
 
 
\textbf{(B)}\ \frac{5}{36} \qquad
 
\textbf{(B)}\ \frac{5}{36} \qquad
 
\textbf{(C)}\ \frac{7}{12} \qquad
 
\textbf{(C)}\ \frac{7}{12} \qquad
Line 9: Line 8:
 
\textbf{(E)}\ \frac{43}{3} </math>
 
\textbf{(E)}\ \frac{43}{3} </math>
  
 +
== Solutions ==
 +
=== Solution 1 ===
 +
Add up the numbers in each fraction to get <math>\frac{12}{9} - \frac{9}{12}</math>, which equals <math>\frac{4}{3} - \frac{3}{4}</math>. Doing the subtraction yields <math>\boxed{\frac{7}{12}\  \textbf{(C)}}</math>
  
== Solution ==
+
=== Solution 2 ===
 
+
Notice that the numerators and denominators of each expression are 3-term arithmetic series. The sum of an arithmetic series is the middle term multiplied with the number of terms. Since each of the arithmetic series have the same number of terms, we can replace the fractions with the middle terms, which gives us <math>\frac{4}{3} - \frac{3}{4} = \frac{7}{12}</math>
  
 
== See also ==
 
== See also ==
 
{{AMC12 box|year=2011|before=First Problem|num-a=2|ab=B}}
 
{{AMC12 box|year=2011|before=First Problem|num-a=2|ab=B}}
 +
{{MAA Notice}}

Latest revision as of 14:12, 19 January 2021

Problem

What is $\frac{2+4+6}{1+3+5} - \frac{1+3+5}{2+4+6}?$

$\textbf{(A)}\ -1 \qquad \textbf{(B)}\ \frac{5}{36} \qquad \textbf{(C)}\ \frac{7}{12} \qquad \textbf{(D)}\ \frac{147}{60} \qquad \textbf{(E)}\ \frac{43}{3}$

Solutions

Solution 1

Add up the numbers in each fraction to get $\frac{12}{9} - \frac{9}{12}$, which equals $\frac{4}{3} - \frac{3}{4}$. Doing the subtraction yields $\boxed{\frac{7}{12}\   \textbf{(C)}}$

Solution 2

Notice that the numerators and denominators of each expression are 3-term arithmetic series. The sum of an arithmetic series is the middle term multiplied with the number of terms. Since each of the arithmetic series have the same number of terms, we can replace the fractions with the middle terms, which gives us $\frac{4}{3} - \frac{3}{4} = \frac{7}{12}$

See also

2011 AMC 12B (ProblemsAnswer KeyResources)
Preceded by
First Problem
Followed by
Problem 2
1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25
All AMC 12 Problems and Solutions

The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions. AMC logo.png

Invalid username
Login to AoPS